Ecosystem services assessment based on land use simulation: A case study in the Heihe River Basin, China - Jing Zhao; Zhuang Shao; Chuyu Xia; Kai Fang; Ran Chen; Jun Zhou (Ecological Indicators, 2022)
Land use and land cover (LULC) changes exert large impacts on key ecosystem services (ESs) in arid areas. This study presents a framework to link LULC change with spatial changes in 3 key ESs in arid areas; this framework can contribute to sustainable ecological environment zoning management. In this study, taking the Heihe River Basin (HRB) as an example, we first assessed the spatiotemporal changes in 3 ESs, including soil conservation (SC), water yield (WY), and carbon storage (CS), from 1995 to 2020 using the InVEST model. Second, we used the (Future Land Use Simulation) FLUS model to predict future land-use variations in 2030 and 2050 under 4 scenarios (Basic Scenario (BS), Low-impact Scenario (LIS), High-impact Scenario (HIS), and Sustainable Development Scenario (SDS)). Third, we assessed the future spatial distributions of the 3 ESs with the InVEST model based on the output raster of the FLUS model. Spatial autocorrelation analysis was applied to ecological zoning management. The results showed that from 1995 to 2020, WY decreased slightly by 0.03%, and SC decreased by 2.6%, mainly in the midstream and upstream regions of the HRB. CS presented a trend of first decreasing by 1.3% from 1995 to 2010 and then increasing by 0.5% from 2010 to 2020; this trend was distributed in the upper reaches. In 2030 and 2050, under the HIS, CS increased by 14.7% and 22.0%, respectively, while WY increased by 0.20% and 0.47%, respectively. Under the SDS, CS increased by 1.1% and 1.3%, WY decreased by 0.21% and 0.45%, and SC decreased by 3.3% and 10%.